2015
DOI: 10.1088/1758-5090/7/1/015014
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of magnetite-based core–shell coated nanoparticles with antibacterial properties

Abstract: We report the fabrication of biofunctionalized magnetite core/sodium lauryl sulfate shell/antibiotic adsorption-shell nanoparticles assembled thin coatings by matrix assisted pulsed laser evaporation for antibacterial drug-targeted delivery. Magnetite nanoparticles have been synthesized and subsequently characterized by transmission electron microscopy and x-ray diffraction. The obtained thin coatings have been investigated by FTIR and scanning electron microscope, and tested by in vitro biological assays, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Functionalized Fe 3 O 4 nanoparticles are usually prepared by wet chemical precipitation from aqueous iron salt solutions by means of alkaline media, like HO − and NH 3 [ 71 , 72 ]. In this case, the AN-extract-functionalized Fe 3 O 4 NPs were synthesized according to previously reported work [ 73 , 74 ] as follows: First, 500 mg of AN extract and 8 mL of NH 4 OH (25%) were added to 200 mL deionized water under stirring. Then, 1 g of FeCl 3 (anhydrous) and 1.6 g of FeSO 4 ·7H 2 O were dissolved in 200 mL of deionized water, and Fe +3 /Fe 2+ solution was dropped into the basic solution of AN extract.…”
Section: Methodsmentioning
confidence: 99%
“…Functionalized Fe 3 O 4 nanoparticles are usually prepared by wet chemical precipitation from aqueous iron salt solutions by means of alkaline media, like HO − and NH 3 [ 71 , 72 ]. In this case, the AN-extract-functionalized Fe 3 O 4 NPs were synthesized according to previously reported work [ 73 , 74 ] as follows: First, 500 mg of AN extract and 8 mL of NH 4 OH (25%) were added to 200 mL deionized water under stirring. Then, 1 g of FeCl 3 (anhydrous) and 1.6 g of FeSO 4 ·7H 2 O were dissolved in 200 mL of deionized water, and Fe +3 /Fe 2+ solution was dropped into the basic solution of AN extract.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of the literature on Fe 3 O 4 activity in relation to S. aureus showed a variety of methodologies and results. 14,16,19,20,65,66 In our work, the broth microdilution method using UV 67 was initially tested, however, the results were not reproducible. Alternatively, the use of the agar dilution method 39 proved to be more reliable and reproducible.…”
Section: Characterization Of Liposomesmentioning
confidence: 92%
“…Several components may constitute the functionalized outer coating depending particularly on the intended application. For example, diverse biological molecules [insulin, nerve growth factor (NGF), ceruloplasmin, elastin, Tat-peptide, folic acid, transferring, lactoferrin, transforming growth factor α (TGF-α), gluthatione (GSH), methotrexate, antibiotics, essential oils, and ascorbic acid, among many others] can be bound to the coating polymer in order to direct them to specific targets [ 11 , 12 , 14 , 21 , 91 , 126 , 127 , 128 , 129 ]. In the cases where it is intended to deliver drugs in specific targets or to make easier the degradation of the nanostructure, the non-specific physical sorption is preferred between the magnetite nanoparticles and the surface-modifying molecule, although non-covalent or covalent bindings may also occur [ 130 ].…”
Section: Superparamagnetic Iron Oxide Nanoparticles Applicationsmentioning
confidence: 99%
“…This result may mean that the therapeutic dose of amoxicillin can be reduced if under functionalized magnetite nanostructures [ 142 ]. The same research team [ 126 ] also reported a prolonged anti-biofilm activity against S. aureus and Pseudomonas aeruginosa in the presence of magnetite nanoparticles stabilized by sodium lauryl sulfate and coated with cefotaxime and cefrom antibiotics.…”
Section: Superparamagnetic Iron Oxide Nanoparticles Applicationsmentioning
confidence: 99%